2023
DOI: 10.3389/fmats.2023.1138313
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of free and forced convections in the flow of radiative viscous fluid with oxytactic microorganisms

Abstract: The prime intend behind the current effort is to explicate flow attributes of magnetically influenced Newtonian fluids toward a stretchable sheet under the novel physical impact of oxytactic microorganisms in a comparative manner for free and forced convections. In addition, modified Fourier and Fick’s laws are implemented to examine the change in temperature and concentration distributions in a more realistic manner by accounting thermal and mass relaxation parameters in the flow. The obtained PDEs are reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Sindhu and Giresha [21] inspected the radiation impression on the tangent fluid passing on a vertical plate. Bilal et al [22] determined the flow behavior of viscous fluid and heat transferal analysis was examined through thermal radiation and testified that the Nusselt number rises for amplifying the radiation and also the density of motile microorganism upwards. The work revealed that the thermal assessment of Sutterby fluid which containing radiation characteristics on a moving sheet was investigated by Bilal et al [23].…”
Section: Introductionmentioning
confidence: 99%
“…Sindhu and Giresha [21] inspected the radiation impression on the tangent fluid passing on a vertical plate. Bilal et al [22] determined the flow behavior of viscous fluid and heat transferal analysis was examined through thermal radiation and testified that the Nusselt number rises for amplifying the radiation and also the density of motile microorganism upwards. The work revealed that the thermal assessment of Sutterby fluid which containing radiation characteristics on a moving sheet was investigated by Bilal et al [23].…”
Section: Introductionmentioning
confidence: 99%
“…The latest studies on stretching cylinder can be found in Refs. [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]).…”
Section: Introductionmentioning
confidence: 99%